2017
DOI: 10.1371/journal.pntd.0005777
|View full text |Cite
|
Sign up to set email alerts
|

Pathological manifestations in lymphatic filariasis correlate with lack of inhibitory properties of IgG4 antibodies on IgE-activated granulocytes

Abstract: Helminth parasites are known to be efficient modulators of their host’s immune system. To guarantee their own survival, they induce alongside the classical Th2 a strong regulatory response with high levels of anti-inflammatory cytokines and elevated plasma levels of IgG4. This particular antibody was shown in different models to exhibit immunosuppressive properties. How IgG4 affects the etiopathology of lymphatic filariasis (LF) is however not well characterized. Here we investigate the impact of plasma and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 87 publications
2
14
0
Order By: Relevance
“…Another interesting finding was the fact that in our model, IgG4 antibodies from Mf+ individuals presented a higher affinity to the Fc portions of IgG1–2 compared to IgG4 antibodies from Mf− and CP individuals. This finding extends our previous observation that functional differences regarding their affinity to FcγRs exist between IgG4 antibodies from LF patients of the different clinical groups (Prodjinotho et al 2017) and suggest that a similar pattern might be applicable for their affinity to Fc fragments of other antibodies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Another interesting finding was the fact that in our model, IgG4 antibodies from Mf+ individuals presented a higher affinity to the Fc portions of IgG1–2 compared to IgG4 antibodies from Mf− and CP individuals. This finding extends our previous observation that functional differences regarding their affinity to FcγRs exist between IgG4 antibodies from LF patients of the different clinical groups (Prodjinotho et al 2017) and suggest that a similar pattern might be applicable for their affinity to Fc fragments of other antibodies.…”
Section: Discussionsupporting
confidence: 90%
“…Due to its molecular and immunological properties, IgG4 is often seen as a blocking antibody (Aalberse et al 2009; Rispens et al 2013; Rispens et al 2009; van der Neut et al 2007). Since, in LF models, IgG4 was shown to be predominant in Mf+ individuals compared to Mf−, CP, and EN (Prodjinotho et al 2017), we hypothesized that IgG4 might be the factor that inhibited the affinity of IgG1 and IgG2 to C1q. To test this hypothesis, we depleted IgG4 from the plasma of Mf+ individuals and analyzed the ability of IgG1 and IgG2 in bulk Mf+ plasma (IgG4+) and IgG4-depleted plasma (IgG4−) to interact with C1q.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that helminth infection drives the sustained expression of T cell inhibitory receptors, which may negatively regulate proliferation and the production of pro-inflammatory cytokines by helminth antigen-specific T cells ( 38 40 ). Because these molecules largely function to prevent over exuberant T cell activation, their essential role in preventing parasite-induced immunopathology have been confirmed in animal studies ( 38 , 41 ). However, the impact of these parasite-induced inhibitory molecules on autoimmune pathology has not been clarified.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, in pemphigus, IgG4 autoantibodies to desmoglein play a direct role in the disruption of the epithelial cell surface, leading to the blistering lesions of the disease (37). Moreover, in lymphatic filariasis, IgG4 antibodies from asymptomatic individuals suppressed granulocytes, whereas IgG4 antibodies from symptomatic patients did not (38). Thus, under certain circumstances, the usual antiinflammatory effects of IgG4 antibodies may be altered, resulting in loss of their usual suppressive function, or these antibodies may develop a direct pathogenic role.…”
Section: Discussionmentioning
confidence: 99%